The Effect of Family Caregiver Empowerment Model Intervention on Resilience in Caregivers of Type 2 Diabetes Mellitus Patients - Anggun Afrix Rozana; Rondhianto; Muhamad Zulfatul A'la (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2025)
Background: Feelings of fatigue and stress can arise in caregivers when caring for patients with type 2 diabetes mellitus (T2DM) due to responsibility, pressure, and increasing demands. Therefore, the ability to bounce back from difficult situations, known as resilience, is needed. Purpose: This study aims to analyze the effect of the Family Caregiver Empowerment Model (FCEM) intervention on the resilience of caregivers of patients with type 2 diabetes mellitus. Methods: This study is a randomized control group pretest and posttest study with a sample of 74 respondents, randomly selected using cluster sampling (treatment = 35, control = 39). The independent variable is FCEM, and the dependent variable is resilience. The instrument used is the Connor-Davidson Resilience Scale 25 (CD-RISC 25) questionnaire. Statistical analysis was performed using the Wilcoxon Signed Rank Test and Independent T-test. Results: The results showed that there was a significant difference in depression scores between the pretest and posttest in both the intervention and control groups (p = 0.000 and p = 0.002, < α = 0.05). Additionally, there was a significant difference in resilience between the intervention and control groups (t = 13.644, p = 0.000). Conclusions: The findings of the study demonstrated the effect of the FCEM intervention on the resilience of caregivers of T2DM patients. It is essential to increase the resilience of family caregivers by providing empowerment as a form of social support.